Nilai-Nilai Pendidikan: Khazanah Pemikiran Plato dan Relevansinya Dengan Tri Dharma Perguruan Tinggi: Educational Values: Plato's Treasure of Thought and Its Relevance to the Tri Dharma of Higher Education - Irsyad, Muhammad; Uma, Yuli Choirul (Jurnal Filsafat Indonesia, 2024)
Academic values are vital for all mankind. It is a necessity that education is not only used to achieve IQ (Intelligence Quotient) but EQ (Emotional Quotient) is also a priority. So it is not surprising that Plato since 400 years B.C. has initiated in such a way how education is carried out by the people who teach and the students who are taught so that both of them achieve true knowledge. This essay was prepared using library research methods with a qualitative descriptive approach. This study uses Plato's philosophy of mind to gain a thorough knowledge of the significance of education, particularly in universities. Of course, various books, scientific articles, and other documents were used to examine the academic principles contained in the Tri Dharma of Higher Education through Plato's ideas. This is what inspires universities to be at the top of the standings in Indonesia's educational strata with its form through Tri Dharma. There is also if the two sources that contain academic values can be implemented in a plenary manner, then it will produce people which derive from civitas academica who are labeled as academic wisdom.